The mediating role of administrative empowerment in the relationship between ethical leadership and job performance in public joint-stock companies - Naji, Fouad Mohammed; Al-Rahoumi, Ahmed Ahmed; Mugahed, Faez Nasser (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate the mediating role of administrative empowerment in the relationship between ethical leadership and job performance within Yemeni public joint-stock companies, which play a vital role in supporting the national economy. Employing a descriptive quantitative approach, the research utilized Structural Equation Modeling (SEM) to analyze data from 433 employees across eight companies. The measurement model demonstrated strong psychometric properties, with outer loadings ≥ 0.70, composite reliability ≥ 0.86, and Average Variance Extracted (AVE) ≥ 0.56. The structural model revealed a significant impact of ethical leadership on administrative empowerment (β = 0.83) and of administrative empowerment on job performance (β = 0.86), while no direct effect was found between ethical leadership and job performance (β = 0.070). However, administrative empowerment showed a strong mediating effect (β = 0.717), explaining 69% of the variance in administrative empowerment and 85% in job performance, indicating high predictive power. The findings underscore the importance of administrative empowerment as a mechanism through which ethical leadership enhances job performance, offering a practical framework for evaluating and improving performance in Yemen’s public companies.